A busca da experiência total do humano na poesia de Alexei Bueno - Bonfá, Carlos Eduardo Marcos [UNESP] (2015)
The research reflects on the inclusion of Alexei Bueno in contemporary Brazilian literature and the objective is to demonstrate through poems analysis and some criticism of the author that the lyric self of Alexei Bueno seeks a total human experience, subjective and simultaneously objectified in history. The main strategy to enter the poetry of Alexei Bueno is to shift the notion of anachronism that still remains in vogue in much of the critical mentality tradition today, which is to obsolescence and uselessness to the present. The other strategy is agambeniana: from the text O que é o Contemporâneo?, you can understand that the anachronism is not a negative temporality, but central to all contemporary. For Agamben, this (mixture of closeness and distance) has its foundation in source (arké) that it deeply pulses. These directions indicate a displacement of the notion of anachronism and allow entering the Alexei Bueno's poetic in order to get the man in his historical character (contingent) and in his essential character, that is, seek man in his integral aspect